Cancer stem cells and their vascular niche: Do they benefit from each other?. Issue 2 (1st October 2016) - Ping, Yi-Fang; Zhang, Xia; Bian, Xiu-Wu
Highlights: CSCs are responsible for initiation, recurrence, therapeutic resistance and spread of malignant tumors. Vascular niche promotes self-renewal of CSCs and protects them from radio-chemotherapy. Tumor microvessels are basement membrane-deficient and enriched with CSC-derived ECs, which facilitate tumor metastasis. CSCs regulate and contribute to the formation of vascular niche. The interaction between CSCs and vascular niche provides new insight into developing cancer therapeutic strategies. Abstract: Cancer stem cells (CSCs) locate in and interact with particular vascular niches to maintain their stemness. CSCs induce, remodel and participate in the formation of microenvironmental niches to facilitate survival, stemness and escape from radio-/chemo-/bio-therapies. Neovasculature in tumor is often basement membrane-deficient and enriched with CSC-derived endothelial cells (ECs) and other mural cells, which may promote tumor invasion and metastasis. The aim of this review is to summarize recent findings about the crosstalk between CSCs and their vascular niches and discuss the potential therapeutic significance.